An Annual Assessment of the Heads' of Educational Institutions Activities - Padgurskytė, Vaida (Jaunųjų mokslininkų darbai, 2020)
In recent years the education system, renewed at all levels, from pre-school education to higher education, has undergone many important changes. Implementing education reforms, the situation has also changed in a general education sector. Each year expectations for educational institutions and requirements for their heads have been increasing. Nowadays the activities and requirements for the heads of educational institutions have fundamentally changed. The heads act following standards for their activities. At the institutional segment, the assessment of heads' activities is relevant since it is aimed at developing their activities as heads-leaders, improving the organisation’s performance and the efficiency of learning programmes, developing and managing human resources, promoting the organisation’s image, improving students' achievement results.
Keywords: educational institution; head of educational institution; assessment of activities